Neoadjuvant chemotherapy improves overall survival in resectable colorectal liver metastases patients with high clinical risk scores—— A retrospective, propensity score matching analysis - Chen, Feng-Lin; Wang, Yan-Yan; Liu, Wei; Xing, Bao-Cai (Frontiers in Oncology, 2022)
Background The use of neoadjuvant chemotherapy (NAC) in resectable colorectal liver metastases (CRLM) patients is controversial. High-risk patients are more likely to benefit from NAC despite its hepatotoxic effects. Since patients with a high tumor burden receive NAC more frequently, previous retrospective studies have imbalanced baseline characteristics. The results of randomized controlled trials are still pending. This study aimed to assess the efficacy of NAC in resectable CRLM patients with high clinical risk scores (CRS) proposed by Fong et al. after balancing baseline characteristics by propensity score matching (PSM). Methods Resectable CRLM patients with high CRS (3-5) undergoing hepatectomy between January 2003 and May 2021 were retrospectively studied. Patients were divided into the NAC and the upfront surgery group. Survival outcomes and surgical outcomes were compared after PSM. Results The current study included 322 patients with a median follow-up of 40 months. After one-to-two PSM, patients were matched into the upfront surgery group (n = 56) and the NAC group (n = 112). Baseline characteristics were balanced after matching. There was no difference in long-term progression-free survival (PFS), while overall survival (OS) from the initial diagnosis was improved in the NAC group (P = 0.048). Postoperative hospital stays were shorter in the NAC group (P = 0.020). Surgical outcomes were similar, including major hepatectomy rate, intraoperative ablation rate, blood loss, operative time, perioperative blood transfusion, positive surgical margin, and postoperative intensive care unit stay. In multivariable analysis, RAS mutation, maximum tumor diameter≥3cm, and no NAC were independent risk factors for OS. The 1-year PFS in the NAC group was improved, although it failed to reach a statistical difference (P = 0.064). Conclusions NAC could improve OS in resectable CRLM patients with high CRS (3-5) and have a shorter postoperative hospital stay.